P=2(l + b)
P=2l + 2b
P-2b=2l
P-2b/2=l
C is your answer
The simultaneous equations are
2x - 7y = 4 (1)
3x + y = -17 (2)
Write (2) as
y = - 3x - 17 (3)
Substitute (3) into (1).
2x - 7(-3x - 17) = 4
2x + 21x + 119 = 4
23x = -115
x = -5
This is the equation obtained after substituting y from the second equation into the first equation.
The solution for y is
y = -3(-5) - 17 = -2
Answer: x = -5
Note: The solution is x = -5, y = -2.
<h3>The value of y is equal to 1.</h3><h3>The value of x is equal to 4.</h3>
Because both equations have a term that will cancel out if they're added together, we're going to add both equations together.
-5x + 5x = 0
13y + 4y = 17y
-7 + 24 = 17
17y = 17
Divide both sides by 17.
y = 1
Now that we have a constant value of y, we can solve for x.
-5x + 13(1) = -7
-5x + 13 = -7
Subtract 13 from both sides.
-5x = -20
Divide both sides by -5.
x = 4
G(x)=(x+3)2 we must find x? so x+3=0 x=-3 we transformation -3 on left
Answer:
500
Step-by-step explanation: